Acute and chronic sleep deprivation in residents: Cognition and stress biomarkers. Issue 2 (28th August 2020) - Choshen‐Hillel, Shoham; Ishqer, Ahmad; Mahameed, Fadi; Reiter, Joel; Gozal, David; Gileles‐Hillel, Alex; Berger, Itai
Abstract: Objectives: Insufficient sleep affects circadian hormonal profiles and inflammatory markers and may modulate attention, executive functioning and decision‐making. Medical professionals and specifically resident physicians, who are involved in long‐term nightshift schedules during their post‐graduate training, are prone to acute and chronic sleep deprivation and disruption, putting them at risk for making medical errors. The aim of the study was to evaluate the impact of chronic and acute‐on‐chronic sleep deprivation and disruption among residents on selected physiological and cognitive measures. Methods: Thirty‐three medical and surgical residents were evaluated twice ‐ at baseline and after a 26‐hour shift. Eighteen young attending physicians who did not engage in nightshift schedules served as controls and were evaluated once. Measures included morning cortisol and high‐sensitivity C‐reactive protein (hs‐CRP), computerised tests of attention and behaviour, the Behaviour Rating Inventory of Executive Function, a risk‐taking questionnaire and the Pittsburgh Sleep Quality Index. Results: Residents, but not attendings, reported chronic sleep disruption and deprivation. Residents at baseline exhibited reduced morning cortisol levels and elevated hs‐CRP levels, compared to attendings. Residents at baseline had impaired global executive function compared to attendings. A nightshift with acute sleep deprivation further reduced residents' executive function. Residents at baseline and after a nightshift demonstrated increased impulsivity and slower processing time than attendings. Residents and attendings did not differ in risk‐taking tendencies which were assessed in a separate cohort. Conclusions: In a real‐life setting, resident physicians exhibit increased low‐grade systemic inflammation (hs‐CRP) and impaired HPA‐axis function. Their chronic sleep curtailment is associated with greater impulsivity, slower cognitive processing, and impaired executive function. Future research is warranted to understand how improving working schedule by increasing sleep duration may minimise the short‐term and potential long‐term risks to physicians in training. Abstract : The authors demonstrate that not only does chronic sleep deprivation impair a variety of mental and physical functions, but some effects are further aggravated by the acute sleep restriction of night calls.